Improvement of Solar Dryers (Texas Journal of Engineering and Technology, 2023)
For thousands of years, people have dried fruits and vegetables in the sun to preserve them for the winter. New technologies have led to a change in methods, but now the growing demand for healthy, inexpensive natural foods and the need for sustainable income are pushing solar drying to the forefront as a useful alternative to artificial food dryers.